Identification of genetic variations in Necator americanus through resequencing by whole genome amplification. Issue 9 (September 2019) - Liu, Yumei; Liu, Hongxuan; Xie, Yuefeng; Zhang, Baohuan; Zou, Xiaoqian; Ou, Meiling; Ye, Xiaohong; Han, Yajing; Wu, Jing; Chen, Xiaojing; Dong, Shirui; Zhu, Kehui; et al.
Objective: To describe a new strategy for the whole genome resequencing of small parasite samples. Methods: Whole genome resequencing was based on a multiple displacement amplification (MDA) method. Sequencing reads were aligned with the reference genome, and a Bayesian model was used to calculate genotype probabilities. De novo genome assembly was conducted, and single nucleotide polymorphisms (SNPs) were detected. Gene ontology (GO) analysis was used to determine connections between SNPs and genes. Results: In total, 64.12% of the parasite genome sequence was mapped to Necator americanus . fa, and 125, 553 SNPs were detected. GO analysis revealed that most SNPs in coding regions were probably associated with common drug targets. Conclusion: These results reveal the feasibility of a new strategy to detect genetic variations of small parasites. This study also provides a proof-of-principle for the molecular classification and epidemiological analysis of other parasites.